Public Perceptions of Household IoT Smart Water “Event” Meters in the UK—Implications for Urban Water Governance - Goulas, Athanasios; Goodwin, Daniel; Shannon, Caitriona; Jeffrey, Paul; Smith, Heather M. (Frontiers in Sustainable Cities, 2022)
Cities around the world are facing water availability challenges, intensified by increasing populations and climate change. Technology, such as household smart meters measuring domestic water consumption, can play a role in demand management, yet a deeper understanding of public expectations and the practicalities of city-wide implementation is required. This paper explores public perceptions of smart water meters that use Internet of Things (IoT) technology and machine learning to profile household water use ‘events’ and anomalies. By leveraging insights from an online survey implemented in the UK (n = 558), this paper explores factors influencing the likelihood of citizens choosing to have this type of meter installed along with potential societal barriers and opportunities. Nearly half of the participants said they would choose to have such a meter installed and logistic regression showed predictive variables were younger ages, being male, those with existing water meters and those with other smart devices. The likelihood of choosing this type of water meter was also associated with preferences to have control over data privacy, whether the meter would reduce water bills and whether it was provided free of charge. We locate these results within other contemporary experiences of smart meters and water grids in urban contexts to discuss practical challenges of using real-time environmental data for urban water governance. Policymakers and water resources planners should continue to monitor public perceptions, implement urban experiments and cost-benefit analyses to better interpret the wider benefits of such technology for behavioural and educational interventions within a more digitised and increasingly data-centric water grid.